(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article provides a scientific-analytical review of the history of development, achievements, existing problems and promising directions of the fruit and vegetable industry in Uzbekistan during the years of independence. The article discusses the transformation of the industry under market conditions, the dynamics of production indicators by regions, clustering processes, and issues of developing processing and export potential. The study is based on regional statistical data, official documents and scientific sources.